Illustrated book design on Asmat tribe culture in Papua: Promoting local cultural awareness among children - Fitri, Nofria Doni; Veruschka, Zophia Aprilia (Sungging: Journal of Innovative, Cultural, Transdisciplinary Art and Kriya Discourse, 2024)
Asmat is one of the largest tribes in Papua. The Asmat tribe is divided into two coastal and inland areas. The Asmat people tend to be fishermen or hunters. However, besides these two professions, a true woodcarver is another profession of this tribe. The uniqueness and high cultural value of this tribal woodcarving art are very well known. However, the development of the era, knowledge and technology resulted in many foreign cultures entering. The entry of foreign cultures into Indonesia quickly influences various lines of people's lives. Therefore, it is essential to introduce native Indonesian cultures to this generation so that they get to know ethnic groups in Indonesia; educational facilities are needed to teach the culture of ethnic groups in Indonesia in a language that children understand, with illustrations that are interesting and evocative. The educational tool is the Asmat Tribe Culture Illustration Book.